Argon plasma coagulation is an effective treatment in cirrhosis- related gastric antral vascular ectasias. (13th March 2011) - Krystallis, C; Hayes, P C; Plevris, J N
Abstract : Introduction: Gastric antral vascular ectasias (GAVE) represent an uncommon cause of upper GI bleeding (UGIB). There is an association with liver cirrhosis and portal hypertension in 30% of the patients, and account for 4% of non-variceal UGIB. GAVE and severe portal hypertensive gastropathy (PHG) are distinctive entities. Treatments aiming to lower portal pressure are usually ineffective to treat cirrhosis-related GAVE. Although thermal ablation techniques are effective in non-cirrhotic GAVE, there is limited data on the value of Argon plasma coagulation (APC) in the treatment of cirrhosis-related GAVE. Aim: To evaluate the efficacy and safety of APC treatment in cirrhotic patients with UGIB due to GAVE. Methods: Cirrhotic patients were retrospectively included in this study over a 10-year period, if they presented with overt or occult bleeding related to GAVE and treated with APC. Success was defined as; control of bleeding, stabilisation of Hb over 100 g/dl, or Hb increase >10% from pretreatment level, and reduction of transfusion requirements >50% in transfusion-dependent patients. Results: 20 cirrhotic patients with GAVE (Group A) treated with APC, (flow 2 l/min, power 45–65 W) were identified and compared with a randomly selected group of 10 non-cirrhotic GAVE patients (Group B). Overall patients' demographics were; M/F 17/13, mean age 71, 13 years. The two groups presented with overt bleeding (60% vs 40%), occult bleeding (40% vs 60%) whereas transfusion was required in (60% vs 80%) in group A and B respectively. Overall endoscopic treatment with APC was successful in 86.6% (85% vs 90% NS) in Groups A and B respectively. The mean number of APC sessions required between the two groups (A vs B) was 3.88 versus 3.5 (NS) median: 2 versus 2. No adverse effects from APC therapy were recorded in any of the patients despite the presence of significant coagulopathy in the majority of the cirrhotic patients. Conclusion: APC proved effective and safe in the treatment of cirrhosis-related GAVE UGIB. Treatment success was not compromised by disease severity or coagulation status. This data suggests that APC should be considered as the treatment of choice in cirrhosis-related GAVE.